Belajar demokrasi di sekolah: Re-orientasi pendidikan dan pengembangan kultur sekolah yang humanis - Suyato, Suyato (Jurnal Civics: Media Kajian Kewarganegaraan, 2016)
This essay explores the factors that cause a lack of effective preparation of citizens supporting the democratic political system carried by educational institutions, especially schools. After describing the global context, in particular the tendency (trend) practices of Citizenship Education that has shifted to the sheer mission preparation productive workforce as it promoted the ideology of neoliberal role strategies educational institutions (schools), not in the setting up of citizens supporting democratic values , further description focuses on the development of the humanist school culture, which the authors believe to be an absolute prerequisite for learning effective democracy. Recently described of learning about democracy effectically, next, it describes theorization of by a description of the importance of critical pedagogy and ended by a description of the change of learning democracy into learning democracy democratically.